A low-profile power converter using printed-circuit board (PCB) power transformer with ferrite polymer composite. - Tang, S.C.
A new design of low-cost and low-profile power transformer is presented in this paper. The manufacturing cost of a power transformer can be reduced using the proposed printed-circuit board (PCB) transformer. The transformer windings are etched on the opposite sides of a double-sided PCB. Self-adhesive ferrite polymer composite (FPC) sheets are stuck on the two PCB surfaces to shield the magnetic flux induced from the transformer windings. The PCB transformer does not require manual winding and bobbin. A power converter prototype employing the PCB transformer has been implemented. The technique of choosing the optimum switching frequency of the power converter using the PCB transformer is addressed in this paper. The maximum power delivered from the prototype is 94 W. The maximum efficiency of the power converter is 83.5%
Keywords: 83.5 percent; 94 W; PCB power transformer; Double-sided PCB; Ferrite polymer composite; Low-profile power converter; Magnetic flux shielding; Manufacturing cost reduction; Optimum switching frequency; Printed-circuit board; Transformer windings